A RANCANGAN SISTEM NOTIFIKASI KEDATANGAN PEMBELI DENGAN SUARA MENGGUNAKAN ARDUINO (Universitas Methodist Indonesia, 2022)
A grocery store is a place to sell various household needs. Which provides necessities such as kitchen needs, bathing needs, school equipment, snacks, and others. A place that provides so many things is certainly not spared from theft by several members of the community. In previous research, is a system for home security. This research focuses on the installation of multisensors at each entrance in the house, which uses buzzer sensors and SMS as outputs. Therefore, to adjust the conditions at the grocery store. The components consist of Arduino UNO R3, ultrasonic sensor, DF Player, LCD, I2C, Speaker, and ESP32-CAM. This system is equipped with the feature of taking photos sent to telegram using the ESP32-CAM. The results of this study are the distance that the sensor can detect is quite far, but as a form of experiment, the author limits the distance to 12cm and will detect objects when they are at a distance of 5cm. The test proves that when the sensor detects an object with the object status coming, the speaker sounds which is connected to the DF Player by playing audio stored on the sdcard. The LCD will display the status of